From precision agriculture to Industry 4.0: Unveiling technological connections in the agrifood sector. Issue 8 (5th August 2019) - Trivelli, Leonello; Apicella, Andrea; Chiarello, Filippo; Rana, Roberto; Fantoni, Gualtiero; Tarabella, Angela
Abstract : Purpose: Circumstances that are have a significant impact on it. In particular, environmental sustainability related to the increase of worldwide population, and market demand for agricultural products (with consumers more and more aware about cultivation and breeding techniques and interested in healthy and high-quality products) represent two of the key challenges that the agricultural sector is going to face in next years. In such a landscape, technological innovations that can support organizations and entrepreneurs to face these problems become increasingly important, and Industry 4.0 is the most striking example. Indeed, the Industry 4.0 paradigm aims to integrate digital technologies into business processes to raise productivity levels and to develop new business models. Accordingly, digital technologies play a similar role in the precision agriculture domain, and the purpose of this paper is to understand if the technologies at the basis of these two paradigms are the same or not. Design/methodology/approach: The present work investigates how the two domains of Industry 4.0 and precision agriculture are connected to one another by analyzing the most used technologies in both the fields in order to highlight common patterns and technological overlaps. To reach such goal, an approach combining manual and automated analysis was developed. Findings: The research work generated three main results: a dictionary of precision agriculture technologies including 324 terms; a graph, describing the connections between the technologies composing the dictionary; and a representation of the main technological clusters identified. Originality/value: These show how the two domains under analysis are directly connected and describe the most important technologies to leverage when approaching digital transformation processes in the agricultural sector.